Is There Room for Prevention? Examining the Effect of Outpatient Facility Type on the Risk of Surgical Site Infection. (19th July 2016) - Parikh, Rishi; Pollock, Daniel; Sharma, Jyotirmay; Edwards, Jonathan
Abstract : OBJECTIVE: We compared risk for surgical site infection (SSI) following surgical breast procedures among 2 patient groups: those whose procedures were performed in ambulatory surgery centers (ASCs) and those whose procedures were performed in hospital-based outpatient facilities. DESIGN: Cohort study using National Healthcare Safety Network (NHSN) SSI data for breast procedures performed from 2010 to 2014. METHODS: Unconditional multivariate logistic regression was used to examine the association between facility type and breast SSI, adjusting for American Society of Anesthesiologists (ASA) Physical Status Classification, patient age, and duration of procedure. Other potential adjustment factors examined were wound classification, anesthesia use, and gender. RESULTS: Among 124, 021 total outpatient breast procedures performed between 2010 and 2014, 110, 987 procedure reports submitted to the NHSN provided complete covariate data and were included in the analysis. Breast procedures performed in ASCs carried a lower risk of SSI compared with those performed in hospital-based outpatient settings. For patients aged ≤51 years, the adjusted risk ratio was 0.36 (95% CI, 0.25–0.50) and for patients >51 years old, the adjusted risk ratio was 0.32 (95% CI, 0.21–0.49). CONCLUSIONS: SSI risk following breast procedures was significantly lower among ASC patients than among hospital-based outpatients. These findings should be placed in the context of study limitations, including the possibility of incomplete ascertainment of SSIs and shortcomings in the data available to control for differences in patient case mix. Additional studies are needed to better understand the role of procedural settings in SSI risk following breast procedures and to identify prevention opportunities. Infect Control Hosp Epidemiol 2016;1–7